THE PERCEPTION OF FERTILE AGE WOMEN, ON EARLY DETECTION OF CA. CERVICAL WITH VISUAL INSPECTION WITH ACETIC ACID METHOD Â AT BPM HJ. DYAH INDRAWATI, SST, TANJANGRONO VILLAGE, DISTRICT NGORO, MOJOKERTO - Purwati, Heni; Janes P, Catherina (JURNAL KEPERAWATAN SEHAT, 2015)
IVA (Visual Inspection withAcetic Acid), is a simple way to detect cervical cancer as early as possible. This tool isso simple because when the examination, do not need to go to the lab. Fertile age women, who do not understand, oral ready understand, on examination IVA negative have negative perception. Compared to those who have really understand and know the benefits of IVA examination. Therefore, this study aims to find out, the perception of fertile age women, on early detection of Ca. Cervical with Visual Inspection with Acetic Acid method (IVA), at BPM Hj. Dyah Indrawati, SST, Tanjangrono Village, District Ngoro, Mojokerto. This study used a descriptive design. The population is, all Fertile age women, in BPM Hj. Dyah Indrawati, SST, Tanjangrono Village, District Ngoro, Mojokerto, which hamounts to 80 people. By using consecutive sampling technique, found that 67 samples. The results showed that, the perception of Fertile age women, concerning the IVA examination at BPM Hj. Dyah Indrawati, SST, TanjangronoVillage, District Ngoro, Mojokerto, mostly negative amount of 37 respondents (55.2%). The negative perception due to lack of information about IVA examination, fear, shame and self-confidence that does not have cervical cancer, willins pection IVA, causing the respondents have a negative perception about the IVA examination.Keywords: Perception, FertileAge Women,earlydetectionof Ca.Serviks, Visual Inspection WithAcetic Acid Method